Psychometric properties of the Copenhagen Burnout Inventory (CBI) in Italian Physicians - Aiello, Edoardo Nicolò; Fiabane, Elena; Margheritti, Simona; Magnone, Stefano; Bolognini, Nadia; Miglioretti, Massimo; Giorgi, Ines (La Medicina del Lavoro, 2022)
This study aimed to standardize the Copenhagen Burnout Inventory (CBI), a psychometrically sound, worldwide-spread tool among Italian physicians. Methods: Nine hundred and fifteen Italian physicians were web-administered the CBI, Patient Health Questionnaire-8 (PHQ-8), Generalized Anxiety Disorder-7 (GAD-7) and General Self-Efficacy Scale (GSE). The present CBI included 18 items (range=19-90) assessing Personal, Work-related and Client-related Burnout. Client-related adaptation was performed. Construct validity, factorial structure (Confirmatory Factor Analysis) and internal consistency were tested. Diagnostic accuracy was assessed simultaneously against the PHQ-8, GAD-7 and GSE. All CBI measures yielded optimal internal consistency (Cronbach’s α=0.90-0.96). Results: The CBI met its original three-factor model (CFI=0.94; TLI=0.93; RMSEA=0.09; SRMR=0.04), was positively related to the PHQ-8 (r=0.76) and GAD-7 (r=0.73), whereas negatively with the GSE (r=0.39) and yielded optimal diagnostics (AUC=0.93; sensitivity=0.91 and specificity=0.85 at the optimal cutoff of 69/90). Conclusion: The CBI is thus a valid, reliable, and normed tool to assess burnout levels in physicians.